The World of Evaluation: Challenges Faced by Student Evaluators - Meghan Billings (Journal of MultiDisciplinary Evaluation)
Background: Performing a high profile evaluation in a world-class organization is a daunting experience for any professional program evaluator. As a student evaluator, it is more than just formidable it has distinctive challenges. Fortunately, professional undertakings provide student evaluators with the experience and tools to overcome these early tests with continuing practice.